145 Investigating the direct implications of the dapa HF trial and the indroducton of sodium-glucose like co-transporter 2 (SGLT2) inhibitors on middlesbrough's heart failure population. (4th June 2021) - Richardson, Samuel; Colman, Joshua; Turley, Andrew
Abstract : Background: DAPA HF was an international, multicentre, parallel group, event-driven, randomized, double-blind, placebo-controlled study in patients with chronic heart failure with reduced ejection fraction (HFrEF), evaluating dapagliflozin versus placebo. This showed individuals with Heart Failure with Reduced Ejection Fraction (HFrEF) (NYHA II-IV, LVEF ≤40%) with or without Type 2 Diabetes Mellitus (T2DM), addition of the SGLT-2 inhibitor dapagliflozin decreased rates of cardiovascular death or worsening heart failure (NNT=21), reduced hospital admissions at 28 days (NNT=27) and all-cause mortality (NNT=43.5). We aim to ascertain the impact the introduction of SGLT2 inhibitors, could have on our local population. Method: A retrospective review of James Cook University Hospitals heart failure database (all patients with LVEF≤ 40%) from 7/3/2019- 7/3/2020. Data recorded: Age, Diabetic Status, Renal Function, HbA1c, HFrEF medication, Diabetes Medication, Heart Failure aetiology. Exclusions: Type 1 Diabetes Mellitus, Deceased, Incomplete data. Data was reviewed by thematic analysis. Results: N=321. Mean Age- 70 years ± 10.5. Non-Diabetic / T2DM = 205/105 (64.2%/35.2%). Heart Failure aetiology: Ischaemic 137 (42.68%), Non-Ischaemic 146 (45.48%), Unknown 38 (11.83%). Renal Function: eGFR<30 mlmin-1= 14, <45 mlmin-1= 55 and <60 mlmin-1= 131. 15 (13%) T2DM patients are on SLGT2 inhibitors. 0 Non-Diabetic patients on SLGT2 inhibitor. Average HbA1c, T2DM patients = 62.7 mmol/mol. HFrEF medication 3 classes: Beta Blockers/ Angiotensin-converting-enzyme inhibitors, Angiotensin II Receptor Blockers or Sacubitril Valsartan/ Mineralocorticoid receptor antagonists. No therapy, 2 (0.62%), Monotherapy: 22 (6.85%), Dual-therapy 156 (48.60%), Triple-therapy 141 (43.93%). Conclusion: Applying DAPA HF inclusion criteria, 292 (90.97%) should be considered for introduction of SGLT2 inhibitors. Renal function isn't a significant barrier to SGLT2 inhibitor introduction. SGLT2 inhibitors aren't widely prescribed in patients with T2DM and HFrEF. Following recent NICE approval, there is scope for local and regional guidelines, directed at primary and secondary care for the prescribing of SLGT2 inhibitors in a HFrEF population. Conflict of Interest: Nil